The Theatre of Identity: Changing Survival Mechanisms of Diasporic Hellenism in South Africa Through Apartheid to the Present Day - Spanoudes, Renos Nicos (Études helléniques / Hellenic Studies, 2008)
An analysis of the Hellenic diasporic experience in South Africa reveals the influence of Classical Greek Theatre. Alongside Greek community churches with halls for weddings and feast days, Hellenic associations, striving to maintain identity in a foreign land, produced plays and organised dance festivals. During the Apartheid years, Greeks were stereotypically perceived as immigrants involved in corner cafés. In the new South Africa, contributions of such minority groups, in fields ranging from legal to medical is acknowledged, and in terms of the arts, Modern Greek diasporic theatre is increasingly reflecting shared angst. Regard for Greek Theatre was and is not confined to original immigrants and subsequent generations of offspring. Nelson Mandela, inspired by Sophocles, staged Antigone’s interrogation by King Creon, with fellow prisoners, while incarcerated on Robben Island. Playwright Athol Fugard immortalised this event in The Island and in Demetos, addressing the tragic realities of masses in a non-democratic society. J. M. Coetzee, recipient of the Nobel Prize for Literature, presented corruption in Waiting for the Barbarians. More recently, Aristophanes’ Ploutos, reworked by the country’s only Greek Day School, resonated with the current challenges facing all South Africans.